PENGARUH AKTIVITAS, LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS TERHADAP DIVIDEN PADA PERUSAHAAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Apriyati Hutami; Mursalim Mursalim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This study aims to analyze the Influence of Activity, Liquidity, Leverage, and Profitability to Dividend on Real Estate Companies Listed In Indonesia Stock Exchange partially. This study uses secondary data in the form of audited financial statements published on the Indonesia Stock Exchange website with a research sample consisting of 39 real estate companies during the period 2010 to 2012. Multiple linear regression analysis method is used to test the hypothesis. Result of research indicate that variable of Total Asset Turn Over (TATO) have positive and significant influence to Dividend Payout Ratio (DPR). Current Ratio (CR) has an insignificant and negative effect on Dividend Payout Ratio (DPR). Debt To Equity Ratio (DER) has a negative and significant effect on Dividend Payout Ratio (DPR). Return On Investment (ROI) has a positive and significant effect on Dividend Payout Ratio (DPR). These results are expected to be a consideration for investors in making investments